Answer:
Step-by-step explanation:
Answer:
nei prossimi giorni, che si è svolto il convegno
the action of moving back and forth quickly and steadily
the distance between one compression and the compression next to it
the action of moving through a material or substance
Answer:
the action of moving back and forth quickly and steadily
Explanation:
hopes this helps :D
Here is the full question:
When a species has several variants of a phenotype passed on from generation to generation, we can form a hypothesis about the genetics of the trait based on Mendelian theories of genetic inheritance. For example, in a two-gene dominant epistatic model, the first gene masks the effect of the second gene, leading to the expression of three phenotype variants. Crossing the dominant and recessive homozygote lines would result in a second generation represented by a mix of dominant, intermediate, and recessive phenotype variants in the expected proportions: and respectively, also called a 12:3: 1 ratio.
Such a model can provide the basis for the null hypothesis in a significance test. A cross of white and green summer squash plants gives the number of squash in the second generation F2: 131 white squash, 34 yellow squash, and 10 green squash. Are these data consistent with a 12: 3: 1 dominant epistatic model of genetic inheritance( white being dominant)?
The null hypothesis for the chi-square goodness-of-fit test is
Answer:
The null hypothesis for the chi-square goodness-of-fit test is :
Step-by-step explanation:
The objective of this question is to state the null hypothesis for the chi-square goodness-of-fit test.
Given that:
There are three colors associated with this model . i,e White , yellow and green and they are in the ratio of 12:3:1
The total number of these color traits associated with this model = 12 + 3 + 1 = 16
Thus ;
The null hypothesis for the chi-square goodness-of-fit test is :
width of the rectangle = b = x
length of the rectangle = l = 8 + 2x
Perimeter of the rectangle = 70cm
Also, perimeter of the rectangle = 2(l + b)
70 = 2[x + (8 + 2x)]
70 = 2(x + 8 + 2x)
70 = 2(3x + 8)
70 = 6x + 16
70 - 16 = 6x
54 = 6x
54/6 = x
9 = x
Therefore, b = x
b = 9cm
l = 8 + 2x
I = 8 + 2×9
I = 8 + 18
I = 26cm
Answer:
2 Superscript three-halves
Step-by-step explanation:
Edge
9514 1404 393
Answer:
cuberoot(a) - 1/tenthroot(a)
Step-by-step explanation:
The applicable rule of exponents seems to be ...
(a^b)^c = a^(bc)
a^-b = 1/a^b
__
Expressing all radicals using rational exponents, we want to simplify ...
__
We have shown two simplified expressions. You can choose the one that matches your requirements. Sometimes we don't want any radicals in the denominator.
Answer:
why is there no picture?